Zinc Excess Triggered Polyamines Accumulation in Lettuce Root Metabolome, As Compared to Osmotic Stress under High Salinity - Rouphael, Youssef; Colla, Giuseppe; Bernardo, Letizia; Kane, David; Trevisan, Marco; Lucini, Luigi (Frontiers in Plant Science, 2016)
Abiotic stresses such as salinity and metal contaminations are the major environmental stresses that adversely affect crop productivity worldwide. Crop responses and tolerance to abiotic stress are complex processes for which ‘-omic’ approaches such as metabolomics is giving us a newest view of biological systems. The aim of the current research was to assess metabolic changes in lettuce (Lactuca sativa L.), by specifically probing the root metabolome of plants exposed to elevated isomolar concentrations of NaCl and ZnSO4. Most of the metabolites that were differentially accumulated in roots were identified for stress conditions, however the response was more intense in plants exposed to NaCl. Compounds identified in either NaCl or ZnSO4 conditions were: carbohydrates, phenolics, hormones, glucosinolates and lipids. Our findings suggest that osmotic stress and the consequent redox imbalance play a major role in determining lettuce root metabolic response. In addition, it was identified that polyamines and polyamine conjugates were triggered as a specific response to ZnSO4. These findings help improve understanding of how plants cope with abiotic stresses. This information can be used to assist decision-making in breeding programs for improving crop tolerance to salinity and heavy metal contaminations.